Defence Against Terrorism: Different Dimensions and Trends of an Emerging Threat - Duyan, Adil (IOS Press, 2014)
This course was designed to have a practical focus for the attendees, many of whom are deeply involved in current counterterrorism operations. As such, not only were lectures presented by knowledgeable people in the field of counterterrorism, but the students also worked in groups to discuss their views regarding the international fight against terrorists. The nine lecturers and 40 students were able to create synergy that enhanced discussion and thereby learning